Pengembangan Bahan Ajar Berbasis E-Book Interaktif (BAJARTIF) Pada Materi Teorema Pythagoras - Millah, Hafidzah Nurul; Zakaria, Perry; Pauweni, Khardiyawan A.Y (Research in the Mathematical and Natural Sciences, 2025)
This research aims to: (1) determine the feasibility of interactive e-book based teaching materials, (2) determine students' responses to the attractiveness of the interactive e-book based teaching materials that have been developed. This research is development research or Research and Development (R&D) using the 4-D (four D) model. This research was carried out at SMP Negeri 1 Kabila. Validation results from material experts and design experts show that the results are worthy of being tested with revisions. Then the teaching materials are tested through 2 stages, namely readability testing and feasibility testing. The average results obtained were 85.33% for the readability test of teaching materials and 81.29% for the feasibility test, 87.47% so that interactive e-book based teaching materials had very positive criteria.